PRINCIPALS' ETHICAL LEADERSHIP PRACTICES AS PREDICTOR OF TEACHERS' JOB PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN DELTA STATE (UNIZIK Journal of Educational Management and Policy, 2026)
The study investigated principals’ ethical leadership practices as predictor of teachers’ jobperformance in public secondary schools in Delta State. Two research questions guided the studyand two null hypotheses were tested at the 0.05 level of significance. A correlational researchdesign was adopted for the study. The population of the study comprised 11,083 secondaryschool teachers in 489 public secondary schools in the 11 education zones of Delta State. Thesample size for this study consisted of 918 teachers drawn using a multistage sampling procedure.Two sets of instruments titled “Principals’ Ethical Leadership Practices Questionnaire (PELPQ)”and “Teachers’ Job Performance Questionnaire (TJPQ)” were used for data collection. Theinstruments were validated by three experts, two from the Department of EducationalManagement and Policy, and one from the Department of Educational Foundations in theMeasurement and Evaluation Unit, Faculty of Education, Nnamdi Azikiwe University.Cronbach's alpha was used for a test of internal consistency of the instruments, which yieldedoverall coefficients of 0.80 for PELPQ and 0.86 for TJPQ respectively. The researcher, togetherwith ten research assistants, collected data for the study using the direct approach method and98% return was recorded. Simple regression was used to answer the research questions and testhypotheses. The findings of the study revealed, among others, that principals’ ethical roleclarification practices is a strong and significant predictor of teachers’ job performance in publicsecondary schools in Delta State. It was also found out that principals’ ethical guidance practicesis a moderate and significant predictor of teachers’ job performance in public secondary schoolsin Delta State. Based on the findings, it was recommended, among others, that Delta State PostPrimary Education Board should organize annual seminar to enlighten and update the knowledgeof principals regarding the engagement in ethical guidance practices to enhance teachers’ jobperformance.
Keywords: Teachers, Principals, Ethical Leadership, Job Performance, Ethical Role Clarification, Ethical Guidance